Mortes por acidentes de transporte terrestre no Brasil: Análise dos sistemas de informaç\~ao do Ministério da Saúde - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper presents the statistics of deaths from road accidents in Brazil in 2013 as well as the evolution of total deaths and mode of transport in the last 15 years using the mortality data of the Ministry of Health. In Brazil killed about 43,000 people each year in car accidents being the motorcycle users are most victims. The text also aims at providing a discussion of general guidelines for necessary public policy to reduce the number of traffic accidents.
Keywords: R41; 330; traffic safety; road transportation; traffic accidents